A DEFENCE OF THE MARGIN OF APPRECIATION AND AN ARGUMENT FOR ITS APPLICATION BY THE HUMAN RIGHTS COMMITTEE. Issue 1 (16th November 2015) - McGoldrick, Dominic
Abstract: The margin of appreciation (MoA) has become the central conceptual doctrine in the institutional and jurisprudential architecture of the European Convention on Human Rights (ECHR). This article critiques the existence and operation of the MoA within the ECHR system and defends its use. It is submitted that as each of the central justifications for the MoA under the ECHR applies equally to the International Covenant on Civil and Political Rights (ICCPR), so the doctrine should be applied by the Human Rights Committee.